KEPEMIMPINAN DEMOKRATIS DALAM PENERAPAN MANAJEMEN BERBASIS SEKOLAH - Reresi, Marsianus (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2018)
This article presents the conceptual study of the democratic leadership role of principals in the implementation of school-based management. This study is very relevant because this study presents alternative leadership of school principals as the main factor in the successful implementation of school-based management.